1994
DOI: 10.1159/000313645
|View full text |Cite
|
Sign up to set email alerts
|

An Anomalous Cleido-Occipitalis Muscle

Abstract: In a Japanese female cadaver, the occipital portion of the trapezius muscle (the cleido-occipitalis) was separated from the rest of the muscle by a triangular gap that resulted from a deficiency of the upper two thirds of the cervical portion on both sides. The right cleido-occipitalis blended distally with the cervical fibers of the trapezius and had a normal insertion into the clavicle. The left cleido-occipitalis intermingled partially with the reduced cervical portion, and some of the conjoint fibers forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The reported incidence of the cleidooccipital muscle ranges from 4.16% to 36.3% (Sarikcioglu et al, 2001;Wood, 1869). The muscle can be also found bilaterally (Rahman & Yamadori, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of the cleidooccipital muscle ranges from 4.16% to 36.3% (Sarikcioglu et al, 2001;Wood, 1869). The muscle can be also found bilaterally (Rahman & Yamadori, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In the region of the posterior triangle of the neck the unusual cleido-occipitalis muscle may be present in peculiar variants (Rahman and Yamadori, 1994;Kwak et al, 2003). Kwak et al (2003) reported a case of cleido-occipitalis forming a flat tendinous arch over the clavicle.…”
Section: Variant Muscular Structuresmentioning
confidence: 99%
“…The cleido-occipitalis cervicalis muscle is an isolated bundle between the trapezius and sternocleidomastoid muscles that appears to arise as a segregation of the common primordium of those muscles (Rahman and Yamadori 1994;Kwak et al 2003; Source: Mori (1964). Source: Mori (1964).…”
mentioning
confidence: 99%